2019
DOI: 10.1088/1361-6463/ab257d
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of a xenon short arc lamp considering the behavior of tungsten vapour evaporated from electrodes

Abstract: The tungsten vapour produced from the electrodes during short arc lamp operation is transported by gas convection and then deposited on the inner quartz bulb wall to form a tungsten thin film, causing the wall to blacken. We have been able to consider important phenomena for the first time by developing a unified numerical simulation model incorporating relevant sub-models. These include the absorption of the radiant energy due to blackening of the lamp and the temporal variation in the lamp parameters. The va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 50 publications
2
16
0
Order By: Relevance
“…In the present paper, we have used a unified numerical simulation model [15] to investigate the factors that affect the short arc lamp characteristics by changing gas species. The influence of the arc voltage, temperature and flow field, radiative efficiency and gas convective pattern and also the blackening location was compared for Xe, Kr and Ar gases and examined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present paper, we have used a unified numerical simulation model [15] to investigate the factors that affect the short arc lamp characteristics by changing gas species. The influence of the arc voltage, temperature and flow field, radiative efficiency and gas convective pattern and also the blackening location was compared for Xe, Kr and Ar gases and examined.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of the model is the same as that of the Xe arc lamp used in the previous study [15], in which the model was validated However, those can be found in our previous work [15]. 31s 溶 接 学 会 論 文 集 第 38 巻(2020)第 2 号…”
Section: Simulation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The three components q (r, i), q (r, j) and q (r, k) can be calculated by equation (28). Thus, the radiation-induced energy source S R used in the energy equation in table 1 is:…”
Section: Radiative Heat Transfermentioning
confidence: 99%
“…The plasma bulk has been treated under local thermodynamic equilibrium (LTE) [9,27,28] since the temperature is high enough to allow high collision frequency between heavy particles and electrons. With continued progress being made in nonequilibrium modeling, the arc plasma has been modeled under both thermal nonequilibrium and chemical nonequilibrium [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%